Comparative evaluation of sedative and anti-nociceptive effects of epidural romifidine, romifidine–lidocaine, and lidocaine in donkeys (Equus asinus) - Marzok, Mohamed; Almubarak, Adel I.; Babiker, Hussein; Kandeel, Mahmoud; El-Hawari, Sayed Fathi; El-khodery, Sabry (Frontiers in Veterinary Science, 2022)
Background: Local and regional anesthetic procedures are valuable tools in veterinary practice. Caudal epidural administration of local anesthetic agents is widely reported for surgical interventions of the tail, anus, rectum, vulva, vagina, urethra, and bladder in the standing horse. Epidural analgesia is also obtained using various drugs such as alpha-2 adrenoceptor agonists, dissociative anesthetics, and opioids. The present study evaluates the anti-nociceptive and sedative effects of epidural administration of romifidine, a romifidine–lidocaine combination, and lidocaine alone in donkeys. Materials and Methods: In a randomized prospective study, twenty-four healthy adult donkeys were assigned to four groups (three experimental and one control; n=6) received either 50 μg/kg of romifidine, 0.30 mg/kg of lidocaine, combined romifidine (50 μg/kg) and lidocaine (0.30 mg/kg) diluted in 0.9% sterile normal saline solution to a total injection volume of 12 ml, or an equivalent volume of sterile saline epidurally. After epidural injection of each treatment, the onset, degree, and duration of sedation and anatomical extension of anti-nociception were documented. Observations began immediately (time 0) pre-administration and at 5, 15, 30, 45, 60, and 30-min intervals subsequently until 210 min after drug injection. Time to onset of perineal analgesia was documented every minute after the epidural injection by evaluating the animal’s response to pinpricks. Results: Only romifidine and romifidine-lidocaine induced mild to moderate sedation. Romifidine, romifidine-lidocaine, and lidocaine induced complete bilateral caudal epidural analgesia with loss of sensation in the perineum, tail, inguinal region, caudal aspect of the upper hind limb, chest areas, and extended distally to the dorsal metatarsal area. Sedation lasted longer (p<0.05) with romifidine (160 ± 15.4 min) than with romifidine-lidocaine (141.6 ± 13.2 min). Longer-lasting analgesia (p<0.05) was obtained with romifidine (158.3 ± 9.8 min) and romifidine-lidocaine (165 ± 9.4 min) than with lidocaine (75.8 ± 8 min). Conclusions: Epidural administration of a single dose of romifidine or a combination of romifidine-lidocaine produced mild to moderate sedation and complete anti-nociception in the perineal and inguinal regions of donkeys. The clinical usefulness of epidural romifidine or romifidine-lidocaine combinations to perform obstetric procedures in donkeys needs to be assessed.